KETERAMPILAN PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI SISWA AUTIS UNTUK MENGEMBANGKAN KECERDASAN EMOSIONAL (EQ) - Raharja, Sigit; Khalim, Sakurun; Mardinawan, Fendi (Early Stage, 2025)
This research aims to understand how skills in learning Islamic Religious Education (PAI) can be used to develop the emotional intelligence of autistic children at SLB Mitra Ananda. Apart from that, this research will also identify indicators of achieving emotional intelligence scores achieved through PAI learning activities at the school. This research uses descriptive qualitative methods to understand and describe a phenomenon in depth. This method does not focus on testing hypotheses, but rather on exploring and interpreting data to provide a comprehensive picture. at SLB Mitra Ananda Karanganyar. This research collects data through three main ways: observation, interviews, and documentation. These methods were chosen to gain a deep and comprehensive understanding of the topic under study. Based on the data analysis carried out, it can be concluded that learning Skills in Islamic Religious Education (PAI) to develop the emotional intelligence of children with Autism Spectrum Disorder (ASD) at SLB Mitra Ananda Karanganyar is implemented through various activities such as Islamic art collage and calligraphy skills, worship skills in this case ablution activities, praying and praying together, as well as visual skills activities. Indicators of achieving emotional intelligence for autistic students are selfregulation, self-awareness, self-motivation, empathy, and social skills. This research concludes that strengthening PAI learning strategies through skills activities is very important for developing the emotional intelligence of ASD students